L'Archivio E-Prints dell'Università di Firenze: prospettive locali e nazionali (Firenze, 10 febbraio 2004) - Cotoneschi, Patrizia (Proceedings e report, 2004)
E-Prints Archive is the institutional archive of electronic documents (e-prints) of the University of Florence: an essential resource for scientific communication. It contains teaching and research documents created by university professors and researchers (learning material, technical reports, dissertations, working papers, preprints and post-prints). The Conference of which the book collects the Proceedings, presented E-Prints Archive, its purposes, its potential for increasing the visibility of the author, of his scientific production and of the institution to which he belongs, contextualising it in the Italian and international perspectives of Open Archives and Digital Library.